Neuroborreliosis: pathogenesis, symptoms, diagnosis and treatment. (March 2011) - Rupprecht, Tobias A; Fingerle, Volker
Lyme disease is the most common human tick-borne disease in the northern hemisphere. This article describes the current knowledge of several aspects of Lyme neuroborreliosis. The epidemiology is reviewed first, with special respect to the difference between European and American disease. Then, the current knowledge about the pathogenesis of Lyme neuroborreliosis is presented, with emphasis on immune evasion strategies. Furthermore, the clinical picture of acute Lyme neuroborreliosis and the frequently discussed post-Lyme disease syndrome are critically discussed. The commonly used diagnostic strategies, as well as the relevance of the lymphocyte transformation test, CD57 + /CD3 - cell count and CXCL13, are presented. Finally, the therapeutic options are described to give a balanced overview of all aspects of this disease.